Sanctity as literature in late medieval Britain - Contzen, Eva von; Bernau, Anke (Manchester : Manchester University Press, 2015)
This title explores how sanctity and questions of literariness are intertwined across a range of medieval genres.
7. Reading classical authors in Capgrave's, Sarah James; 8. Lydgate's saintly poetics, Anke Bernau; 9. Narrating vernacular sanctity: the Scottish Legendary as a challenge to the 'literary turn' in fifteenth-century hagiography; 10. Reforming sanctity: the Digby Mary Magdalen and Lewis Wager's Life and Repentaunce of Marie Magdalene, Tamara Atkin; 11. The humanist grammar of sanctity in the early Lives of Thomas More, Anna Siebach Larsen; 12. Afterword: calendar time in balade form, Catherine SanokBibliography; Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (JSTOR, viewed on April 21, 2016).
English.
JSTOR
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Religion in literature; Saints in literature; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Religion dans la littérature.; Saints dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English literature -- Middle English; Religion in literature; Saints in literature; 1100-1500; British Isles; Sanctity; literariness; medieval literature; poetics; Literary criticism; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.